Origin of fibrosing cells in systemic sclerosis. Issue 6 (November 2015) - Ebmeier, Sarah; Horsley, Valerie
Abstract : Purpose of review: Systemic sclerosis, an autoimmune disease of unknown origin, is characterized by progressive fibrosis that can affect all organs of the body. To date, there are no effective therapies for the disease. This paucity of treatment options is primarily because of limited understanding of the processes that initiate and promote fibrosis in general and a lack of animal models that specifically emulate the chronic nature of systemic sclerosis. Most models capitulate acute injury-induced fibrosis in specific organs. Yet, regardless of the model a major outstanding question in the field is the cellular origin of fibrosing cells. Recent findings: A multitude of origins have been proposed in a variety of tissues, including resident tissue stroma, fibrocytes, pericytes, adipocytes, epithelial cells and endothelial cells. Developmentally derived fibroblast lineages have recently been elucidated with fibrosing potential in injury models. Increasing data support the pericyte as a fibrosing cell origin in diverse fibrosis models and adipocytes have recently been proposed. Fibrocytes, epithelial cells and endothelial cells also have been examined, although data do not as strongly support these possible origins. Summary: In this review, we discuss recent evidence arguing in favor of and against proposed origins of fibrosing cells in diverse models of fibrosis. We highlight outstanding controversies and propose how future research may elucidate how fibrosing cells arise and what processes can be targeted in order to treat systemic sclerosis.